Letter (copy) : International Brigade - Tewson, Vincent
034-0180-001 HVT/ET/866. Secretary's. 11th May, 1937. Mr. R. Cumming, The Edinburgh and District Joint Committee for Spanish Relief, 51, Glendevon Terrace, Murrayfield, EDINBURGH, 12. Dear Mr. Cumming, INTERNATIONAL BRIGADE. I have your letter of the 7th May containing the resolution of your Committee. I may say that the suggestion contained in your resolution has already received consideration, but finally it was felt that as our Fund has been raised specifically for the assistance of the Spanish workers the proposal could not be accepted. It is known, however, that in many cases the dependents of Trade Unions who have gone to Spain have received assistance through the voluntary collections of members of their branch. Yours sincerely, Assistant Secretary. 292/946/34/180